2014
DOI: 10.5012/bkcs.2014.35.10.2911
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Interconversion of Acetylcholine Conformers

Abstract: The gas phase structures, energetics, and interconversion pathways of five lowest energy conformers of acetylcholine were examined employing the B3LYP, MP2, and CCSD(T) methods in conjunction with diverse basis sets including the correlation consistent aug-cc-pVDZ and aug-cc-pVTZ basis sets. It is found that use of adequate basis set containing proper polarization and diffuse functions capable of describing the floppy potential energy surface of acetylcholine is important in correctly predicting the relative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In recent decades, computational studies on ACh conformational properties in aqueous solution have dominated. They aim to determine the reactive sites of ACh conformers, [28] the conformational changes’ pathway, [29] the fluorination effect to conformational changes, [30] hydration features, [31] and the features of ACh conformers paired to ions in biological media [32] . In our previous work, we demonstrated that two groups of ACh conformers, capable of undergoing hydrolysis without being preceded by conformational changes, have an energy difference of 8 kcal/mol [33] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, computational studies on ACh conformational properties in aqueous solution have dominated. They aim to determine the reactive sites of ACh conformers, [28] the conformational changes’ pathway, [29] the fluorination effect to conformational changes, [30] hydration features, [31] and the features of ACh conformers paired to ions in biological media [32] . In our previous work, we demonstrated that two groups of ACh conformers, capable of undergoing hydrolysis without being preceded by conformational changes, have an energy difference of 8 kcal/mol [33] .…”
Section: Introductionmentioning
confidence: 99%
“…The dependency is stronger when the reaction involves an enzyme as a catalyst [14,15]. In the ACh + case, at least three conformers have been investigated to understand their stability and the interconversion among the conformers and to explore the fluorination and solvent effects on each of them [16][17][18][19][20][21][22][23][24][25][26][27]. However, to the best of our knowledge, studies of ACh + conformers remain limited to its stability as an individual molecule.…”
Section: Introductionmentioning
confidence: 99%